THE ROLE OF TEACHERS AS CULTURAL COMMUNICATORS IN STRENGTHENING THE CHARACTER OF PANCASILA STUDENT PROFILES AMONG HINDU STUDENTS IN CATHOLIC BASED SCHOOLS IN DENPASAR CITY - Ni Nengah Ulandari , (JKKB: Jurnal Kajian Komunikasi Budaya (JCCS: Journal of Cultural Communication Studies), 2025)
Character strengthening is a crucial aspect of modern education, particularly in shaping students with noble character aligned with the values of Pancasila. In the context of Catholic-based schools in Denpasar City, teachers hold an essential role as cultural communicators who bridge Hindu spiritual values with national values embodied in the Pancasila Student Profile. This study aims to describe the role of teachers as cultural communicators in strengthening the character of Hindu students, the challenges encountered, and the implications arising for students’ character formation. The theoretical framework applied in this study includes George Herbert Mead’s Role Theory, Jean Piaget and Lev Vygotsky’s Constructivism Theory, as well as the Value and Ethics Theory of Clyde Kluckhohn and Immanuel Kant. This research employs a qualitative approach with a phenomenological design. Data were collected through non-participatory observation, structured interviews, and documentation, and analyzed using data reduction, data presentation, and conclusion drawing techniques. The results indicate that teachers act as facilitators, mediators, and role models in communicating character values such as religiosity, tolerance, cooperation, independence, and critical reasoning. The main challenges faced include limited instructional time and students’ low critical reasoning ability, which are addressed through adaptive digital-based communication strategies and dialogical approaches. Consequently, Hindu students demonstrate improvement in sraddha (faith), tolerance, cooperation, independence, and creativity in expressing Hindu cultural values that are in harmony with Pancasila.